PENGEMBANGAN E –LKPD BERBASIS APLIKASI QUIZIZ PADA MUATAN IPA MATERI EKOSISTEM DI KELAS V SD NEGERI 149/VIII MUARA TEBO KABUPATEN TEBO - Fitriyani; Amril; Antik Estika Hader (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low scor in Natural science of students and the previous use of thematic books es a learning media, especially in the subjet Ecosystem, therefore, there is a need for an improvent in the learning process to anhance student’s learning outcomes by using a teaching media the can make student’s active and interactive during the learning proscess. This research adopts the ADDIE model. The ADDIE model consists of five stages of Developmen: Analyze, Desing, Development, Implementation, and evaluation. The first stage is the Analyze stage, where the need for development is analyze,the nex stage is the where a product to development is desinged. The com development stage, aimed t, producing the privously desingd product. The implementation stage follows, where devlopment productsis implemented. Lastly, the evaluation stage involves evaluating, the development product. The assesment results of the quizizz learning media, validated by there validators, yielded an average score 96% categorized as hing valid . of the quizizz learning media is considered by teachers resultes a precentage 90,5%, categorized as hinghly practical in terrms of ase of use anf time efficiency. The particlity tes involving 32 students who used the development fot topic 1 showed a completion rate 87,2% students, topic 2 had a completion rate of 94,4% had a complection rate of 94,2% media was categori as hingky pratical in trems of ase of use and time effcienci. It was also deemed hingly effectife.